Impact of Parental Supervision on Unintentional Injuries among Under-5 Children in North India: A Community-based Cross-sectional Study. - Singla, Priyanka; Halder, Pritam; Gupta, Bhupesh; Mittal, Anshu (Indian Journal of Community Medicine)
Background: Unintentional injuries (UIs) raise the death rate of children under 5 by a considerable margin, making them a serious public health concern that may be improved by parental supervision. Measuring the effect of parental supervision on UIs among under-5 children in North India was the aim of the study. Materials and Methods: A community-based cross-sectional study was conducted on a simple random sample in the field practice area of the institution from May 2019 to April 2020. Household with under-5 children was taken as a sampling unit. Parental supervisory behavior was measured using the Parent Supervision Attributes Profile Questionnaire (PSAPQ). Chi-square analysis was used to assess the variation of variables across urban and rural areas. Logistic regression was done to explore the association between unintentional injuries among under-5 children and parental supervision. Results: The prevalence of UIs among under-5 children in 280 households was 96.43%, most of which were due to falls (90.71%). The prevalence of cut injury (3.03%), crush injury (2.42%), and suffocation/choking (1.21%) was higher in the rural settings. History of the previous injury was present in 237 (87.8%) subjects with an unfavorable median cutoff score of parental supervision (P value 0.011). Favorable parental supervision was a significant protective factor (odds ratio 0.052, 95% CI 0.028–0.076) given UIs in under-5 children. Conclusion: This research revealed the positive impact of parental supervision on UIs among under-5 children in both rural and urban settings of North India.